Study on benefit of guide vane for vertical axis wind - Haneen S.; Roslan E.; Akhiar A.; Zamri F.; Salleh F.; Isa R.; Shamsuddin A.H. (Institute of Physics Publishing, 2023)
Flow simulation; Tall buildings; Turbulence; Wind; Flow charac-teristics; High rise building; Optimum angle; Power out put; Turbulence intensity; Vertical axis; Vertical axis wind turbines; Wind velocities; Wind turbines